Laterally substituted biphenyl benzoates ‒ synthesis and mesomorphic properties. Issue 4 (16th March 2021) - Cigl, Martin; Hampl, František; Svoboda, Jiří; Podoliak, Natalia; Stulov, Sergei; Kohout, Michal; Novotná, Vladimíra
ABSTRACT: We have synthesised several series of dialkoxy-terminated biphenyl benzoates with lateral substituents (X = F, Cl) in the vicinity of the ester linking group, varying the length of the terminal alkyl chains. The aim was to study mesomorphic properties of these new compounds and compare them with the previously reported analogous phenyl biphenylcarboxylates, which possess reverse orientation of the ester linking group. The studied compounds were characterised by differential scanning calorimetry, polarising optical microscopy and birefringence measurements. For selected homologues, the type of mesophases was confirmed by x-ray scattering analysis. We calculated the dipole moments and suggested its correlation with the preference of tilted smectic phases in studied biphenyl benzoates. Generally, lateral substitution causes the drop of phase transition temperatures as well as melting points, giving rise to mesophases in a wide temperature range, in several cases down to the room temperature. Graphical Abstract: